Internal and External Factors Eﬀects towards Return on Assets in Indonesian Foreign Exchange Sharia Bank - Rizal Rizal; Farid Ahmad Marlion; Himyar Pasrizal; Rini Anita (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2021)
This study aims to analyze the inﬂuence of internal factors such as ﬁnancing and third-party funds, as well as external factors including inﬂation, BI, and exchange rate against Return On Asset (ROA) at Indonesian Foreign Exchange Sharia Bank. Furthermore, the library research was used and quantitatively described. Also, using the total sampling technique, the research team obtained six sample banks, namely Bank Mega Syariah, Muamalat Indonesia, Panin Dubai Syariah, BNI Syariah, BRI Syariah, and Bank Syariah Mandiri. The data include Balance Sheet and Proﬁt, Loss Financial Statements, as well as the published reports on inﬂation, BI, or exchange rates obtained in a quarterly period from 2015 to 2019. According to the F-test, there was a signiﬁcant inﬂuence between the independent variables (Financing, Third Party Funds, Inﬂation, BI, and Exchange Rates) on the dependent (ROA). Meanwhile, the t-test showed there was no signiﬁcant eﬀect of partial financing, Third Party Funds, BI rate (X ), and Kurs (X ) on the ROA. Therefore, this study showed there was an increase in ROA because the society involves in ﬁnancing due to high inﬂation.